2000
DOI: 10.1029/2000ja900017
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation of lower hybrid waves in the Earth's ionosphere: A model analysis

Abstract: Abstract. Lower hybrid wave cavities detected by the Freja satellite are analyzed. On the basis of simple statistical arguments by use of signals from two density probes, it is possible to obtain rather general results concerning the individual shapes of these cavities. In particular, it is demonstrated that a cylindrically symmetric Gaussian density depletion seems to give a very good fit for a vast majority of cases. The validity of this model is shown to give a great simplification in the interpretation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(71 citation statements)
references
References 22 publications
6
65
0
Order By: Relevance
“…The spatial structure of the plasma density associated with these oscillations is like filaments, which extend all along the length of the simulation plasma parallel to Bo, but they are quite thin transverse to Bo. We have shown that the major features of Freja data on LHSS [see Hoymork et al, 2000] are explainable in terms of the electrostatic ELF wave structure, including the upper and lower bounds on the perpendicular scale length and their perpendicular motion.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The spatial structure of the plasma density associated with these oscillations is like filaments, which extend all along the length of the simulation plasma parallel to Bo, but they are quite thin transverse to Bo. We have shown that the major features of Freja data on LHSS [see Hoymork et al, 2000] are explainable in terms of the electrostatic ELF wave structure, including the upper and lower bounds on the perpendicular scale length and their perpendicular motion.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…It has been shown by Høymork et al (2000) that the measured density profiles of the lower hybrid cavities agree well with a Gaussian shape. We may then write a typical profile of a density depletion as…”
Section: Gaussian Cavitiesmentioning
confidence: 52%
“…The data in Fig. 3 are taken from Høymork et al (2000) and show the widths and depths of the cavities. We have superimposed contours of maximum k z (in units of m −1 ), for different b (1/e-width) and (relative depth), from relation (41).…”
Section: Application To Freja Statisticsmentioning
confidence: 99%
See 2 more Smart Citations